Medicinal Plants and Their Traditional Uses in Ramkot Village, Kathmandu Nepal - Silwal, Gautam Ratna (Patan Pragya, 2020)
This study aimed to document the traditional medicinal knowledge of local people of Ramkot village about plants to cure various diseases. Primary data were collected from old aged people of village by using semi structured interview of Key informants. A total of 51 medicinal plants belonging to 38families and 51 genera were documented to treat different diseases and injuries. The highest (29) number of medicinal plants were herbs and lowest (2) were climbers. Majority of them were used to treat gastrointestinal disorders. The study area was found to be rich in plant resources and the old aged people have ample knowledge on the use of medicinal plants. But young generation is not interested about herbal medicine due to easy access of hospitals and modern medical facilities. Due to lack of proper documentation, conservation and cultivation practices, many useful plant species are at risk of extinction in this village.